An Analysis Of Influencer Endorsements, User Reviews, And App Features On Customer Purchasing Decisions In Online Shops Shopee Medan City - Kartika Novelia Nababan; Megasari Gusandra Saragih; Yana Diana (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study was to determine whether influencer endorsements, user reviews, and app features influence customer purchasing decisions at the Shopee online shop in Medan City. The research method was quantitative associative research with the help of SPSS. This study used multiple linear regression. The sample in this study consisted of 96 respondents. Primary data collection used a questionnaire. The results showed that influencer endorsements, user reviews, and app features had a positive and significant influence on customer purchasing decisions at the Shopee online shop in Medan City.